Sikap Mahasiswa Terhadap Denominasi dan Redenominasi Rupiah - Zamroni, Zamroni (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2017)
The purpose of this study was to describe college student attitudes (positives or negatives) to denomination and redenomination issues of Rupiah. Study conducted by combining survey and thought experiment methods on 70 college students with 4 cases as treatment materials and 4 attitude scales as respon measurements which were valid and reliable. Result revealed that college students 89% would like to choose the smaller denomination, 57% respons negatively to negative effects of denomination, 20% respons negatively to the weakness of Rupiah competitiveness, and 24% respons positively to the redenomination of Rupiah. Weakness of Rupiah on the foreign currency impacts to the low collective self-esteem of Indonesian college students.